Retraction: A New Approach for Testing Engagement Characteristics of Clutch (J. Phys.: Conf. Ser. 1885 022027). Issue 2 (April 2021) - Zou, Xinyu; Wang, Yang
Abstract : It has come to the attention of IOP Publishing that this article should not have reached publication because the paper contains a number of fundamental errors in the initial data, calculation, and conclusion which has led to the findings being unreliable. Consequently, this paper has been retracted by IOP Publishing. The authors agree to this retraction. Retraction published: 15 September 2021